Discrimination of three Termitomyces species by HS-GC-IMS volatile profiles combined with biomarkers - Qianqian Tao; Asanka R. Bandara; Rohan S. Dassanayake; Jianchu Xu; Heng Gui; Itthayakorn Promputtha; Peter E. Mortimer; Yuwei Hu (Food Chemistry, 2026)

Elucidation of the biodegradation pathways of polyurethane and polyethylene terephthalate by a Fusarium strain enriched from soil-plant systems - Eyalira Jacob Okal; Yanfei Wu; Shahid Iqbal; Zhaorui Liu; Yuwei Hu; Na Hu; Tingfang Zhong; Jingxian Li; Dongmei Yu; Bishal Gurung; Dong Liu; Peter Mortimer; et al. (Bioresource Technology, 2025)

Unveiling fungal degradation pathways for polyurethane and polyethylene through enrichment cultures and metabolic analysis - Eyalira Jacob Okal; Jie Zhou; Yanfei Wu; Tingfang Zhong; Yue Tang; Zhengyu Sun; Ruifang Xu; Yuwei Hu; Na Hu; Jingxian Li; Samantha C. Karunarathna; Peter E. Mortimer; et al. (International Biodeterioration & Biodegradation, 2025)

Cuphophyllus lijiangensis sp. nov. ( Hygrophoraceae , Agaricales ) from Yunnan, China - Lei Ye; Peter E. Mortimer; Song‐Ming Tang; Qianqian Tao; Guiqing He; Wengao Yang; Yuwei Hu (New Zealand Journal of Botany, 2025)
A new species of Cuphophyllus ( Hygrophoraceae , Agaricales ) was discovered in mixed coniferous and broad‐leaved forests (Pinaceae and Fagaceae) and grassland margins in Lijiang, North‐west Yunnan, and South‐west China. The species is described using morphological and molecular methods. Based on on‐site habitat observation data and a literature review, the novel species is best described as a saprobic macrofungus that thrives in soil humus within mixed pine forests or grasslands. The basidiomata of the novel species exhibit macroscopic similarities to C. virgineus ; however, C. lijiangensis sp. nov. differs primarily in having a smaller pileus, shorter stipe, larger basidiospores, and an intricate trichoderm pileipellis. Phylogenetic analysis, based on the combined rDNA internal transcribed spacer (ITS), nuc28S rDNA (28S), and RNA polymerase II subunit 2 ( rpb 2) genes, places C. lijiangensis in a clade with C. virgineus , C. borealis , C. yacurensis , and C . russocoriaceus . Both morphological characteristics and phylogenetic data support C. lijiangensis as a distinct new species within Cuphophyllus . This study provides a comprehensive description of the new species, colour photographs of basidiomata, micromorphological structures, and a phylogenetic tree to show the position of the new species.

Morphology, phylogeny, and polyurethane degrading ability of Lasiodiplodia iraniensis and Mortierella alpina - Rui-Fang Xu; Saowaluck Tibpromma; Samantha C. Karunarathna; Kevin D. Hyde; Chayanard Phukhamsakda; Eyalira J. Okal; Dong-Qin Dai; Ekachai Chukeatirote; Sehroon Khan; Abdallah M. Elgorban; Peter E. Mortimer (New Zealand Journal of Botany, 2024)

Continental-scale insights into the soil microbial co-occurrence networks of Australia and their environmental drivers - Heng Gui; Martin Breed; Yan Li; Qiang Xu; Jianbo Yang; Dhanushka N. Wanasinghe; Yunju Li; Jianchu Xu; Peter Mortimer (Soil Biology and Biochemistry, 2023)

Estimating the concentration of total suspended solids in inland and coastal waters from Sentinel-2 MSI: A semi-analytical approach - Dalin Jiang; Bunkei Matsushita; Nima Pahlevan; Daniela Gurlin; Cédric G. Fichot; Joshua Harringmeyer; Giulia Sent; Ana C. Brito; Vanda Brotas; Mortimer Werther; Veloisa Mascarenhas; Matthew Blake; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Reviewing the contributions of macrofungi to forest ecosystem processes and services - Allen Grace T. Niego; Sylvie Rapior; Naritsada Thongklang; Olivier Raspé; Kevin D. Hyde; Peter Mortimer (Fungal Biology Reviews, 2023)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Genome Wide Identification of the MLO Gene Family Associated with Powdery Mildew Resistance in Rubber Trees (Hevea brasiliensis) - Kapila K. Liyanage; Sehroon Khan; Venura Herath; Siraprapa Brooks; Peter E. Mortimer; Sadia Nadir; Kevin D. Hyde; Jianchu Xu (Tropical Plant Biology, 2020)

Taxonomic and phylogenetic characterizations reveal three new species of Mendogia (Myriangiaceae, Myriangiales) - Hong-Bo Jiang; Rungtiwa Phookamsak; Jianchu Xu; Samantha C. Karunarathna; Peter E. Mortimer; Kevin D. Hyde (Mycological Progress, 2020)

Many unreported crop pests and pathogens are probably already present - Daniel P. Bebber; Elsa Field; Heng Gui; Peter Mortimer; Timothy Holmes; Sarah J. Gurr (Global Change Biology, 2019)
Invasive species threaten global biodiversity, food security and ecosystem function. Such incursions present challenges to agriculture where invasive species cause significant crop damage and require major economic investment to control production losses. Pest risk analysis (PRA) is key to prioritize agricultural biosecurity efforts, but is hampered by incomplete knowledge of current crop pest and pathogen distributions. Here, we develop predictive models of current pest distributions and test these models using new observations at subnational resolution. We apply generalized linear models (GLM) to estimate presence probabilities for 1,739 crop pests in the CABI pest distribution database. We test model predictions for 100 unobserved pest occurrences in the People's Republic of China (PRC), against observations of these pests abstracted from the Chinese literature. This resource has hitherto been omitted from databases on global pest distributions. Finally, we predict occurrences of all unobserved pests globally. Presence probability increases with host presence, presence in neighbouring regions, per capita GDP and global prevalence. Presence probability decreases with mean distance from coast and known host number per pest. The models are good predictors of pest presence in provinces of the PRC, with area under the ROC curve (AUC) values of 0.75–0.76. Large numbers of currently unobserved, but probably present pests (defined here as unreported pests with a predicted presence probability >0.75), are predicted in China, India, southern Brazil and some countries of the former USSR. We show that GLMs can predict presences of pseudoabsent pests at subnational resolution. The Chinese literature has been largely inaccessible to Western academia but contains important information that can support PRA. Prior studies have often assumed that unreported pests in a global distribution database represent a true absence. Our analysis provides a method for quantifying pseudoabsences to enable improved PRA and species distribution modelling.

First successful domestication and determination of nutritional and antioxidant properties of the red ear mushroom Auricularia thailandica (Auriculariales, Basidiomycota) - Asanka R. Bandara; Samantha C. Karunarathna; Peter E. Mortimer; Kevin D. Hyde; Sehroon Khan; Pattana Kakumyan; Jianchu Xu (Mycological Progress, 2017)

Postnatal LPS Challenge Impacts Escape Learning and Expression of Plasticity Factors Mmp9 and Timp1 in Rats: Effects of Repeated Training - Alexander Trofimov; Tatyana Strekalova; Niall Mortimer; Olga Zubareva; Alexander Schwarz; Evgeniy Svirin; Aleksei Umriukhin; Andrei Svistunov; Klaus-Peter Lesch; Victor Klimenko (Neurotoxicity Research, 2017)

Soil respiration under three different land use types in a tropical mountain region of China - Jun-jie Wu; Stefanie Daniela Goldberg; Peter Edward Mortimer; Jian-chu Xu (Journal of Mountain Science, 2016)

Indigenous trees restore soil microbial biomass at faster rates than exotic species - Chun Li; Ling-Ling Shi; Anne Ostermann; Jianchu Xu; Yunju Li; Peter E. Mortimer (Plant and Soil, 2015)

Intensive agriculture reduces soil biodiversity across Europe - Maria A. Tsiafouli; Elisa Thébault; Stefanos P. Sgardelis; Peter C. de Ruiter; Wim H. van der Putten; Klaus Birkhofer; Lia Hemerik; Franciska T. de Vries; Richard D. Bardgett; Mark Vincent Brady; Lisa Bjornlund; Helene Bracht Jørgensen; et al. (Global Change Biology, 2015)
Soil biodiversity plays a key role in regulating the processes that underpin the delivery of ecosystem goods and services in terrestrial ecosystems. Agricultural intensification is known to change the diversity of individual groups of soil biota, but less is known about how intensification affects biodiversity of the soil food web as a whole, and whether or not these effects may be generalized across regions. We examined biodiversity in soil food webs from grasslands, extensive, and intensive rotations in four agricultural regions across Europe: in Sweden, the UK , the Czech Republic and Greece. Effects of land‐use intensity were quantified based on structure and diversity among functional groups in the soil food web, as well as on community‐weighted mean body mass of soil fauna. We also elucidate land‐use intensity effects on diversity of taxonomic units within taxonomic groups of soil fauna. We found that between regions soil food web diversity measures were variable, but that increasing land‐use intensity caused highly consistent responses. In particular, land‐use intensification reduced the complexity in the soil food webs, as well as the community‐weighted mean body mass of soil fauna. In all regions across Europe, species richness of earthworms, Collembolans, and oribatid mites was negatively affected by increased land‐use intensity. The taxonomic distinctness, which is a measure of taxonomic relatedness of species in a community that is independent of species richness, was also reduced by land‐use intensification. We conclude that intensive agriculture reduces soil biodiversity, making soil food webs less diverse and composed of smaller bodied organisms. Land‐use intensification results in fewer functional groups of soil biota with fewer and taxonomically more closely related species. We discuss how these changes in soil biodiversity due to land‐use intensification may threaten the functioning of soil in agricultural production systems.

The dual symbiosis between arbuscular mycorrhiza and nitrogen fixing bacteria benefits the growth and nutrition of the woody invasive legume Acacia cyclops under nutrient limiting conditions - Peter E. Mortimer; Marcellous R. Le Roux; Maria A. Pérez-Fernández; Vagner A. Benedito; Aleysia Kleinert; Jianchu Xu; Alexander J. Valentine (Plant and Soil, 2013)

Arbuscular mycorrhiza maintains nodule function during external NH 4 + supply in Phaseolus vulgaris (L.) - Peter E. Mortimer; Maria A. Pérez-Fernández; Alex J. Valentine (Mycorrhiza, 2012)

Erratum to: Linkage and sequence analysis indicate that CCBE1 is mutated in recessively inherited generalised lymphatic dysplasia - Fiona Connell; Kamini Kalidas; Pia Ostergaard; Glen Brice; Tessa Homfray; Lesley Roberts; David J. Bunyan; Sally Mitton; Sahar Mansour; Peter Mortimer; Steve Jeffery (Human Genetics, 2010)

Linkage and sequence analysis indicate that CCBE1 is mutated in recessively inherited generalised lymphatic dysplasia - Fiona Connell; Kamini Kalidas; Pia Ostergaard; Glen Brice; Tessa Homfray; Lesley Roberts; David J. Bunyan; Sally Mitton; Sahar Mansour; Peter Mortimer; Steve Jeffery (Human Genetics, 2010)

Critically endangered hawksbill turtles: molecular genetics and the broad view of recovery - JEANNE A. MORTIMER; MARYDELE DONNELLY; ANNE B. MEYLAN; PETER A. MEYLAN (Molecular Ecology, 2007)

Whose turtles are they, anyway? - JEANNE A. MORTIMER; PETER A. MEYLAN; MARYDELE DONNELLY (Molecular Ecology, 2007)
The hawksbill turtle ( Eretmochelys imbricata ), listed since 1996 by the IUCN as Critically Endangered and by the Convention on International Trade in Endangered Species (CITES) as an Appendix I species, has been the subject of attention and controversy during the past 10 years due to the efforts of some nations to re‐open banned international trade. The most recent debate has centred on whether it is appropriate for Cuba to harvest hawksbills from shared foraging aggregations within her national waters. In this issue of Molecular Ecology , Bowen et al . have used molecular genetic data to show that such harvests are likely to have deleterious effects on the health of hawksbill populations throughout the Caribbean.

Lymphoedema-distichiasis and FOXC2: unreported mutations, de novo mutation estimate, families without coding mutations - Carolyn Sholto-Douglas-Vernon; Rachel Bell; Glen Brice; Sahar Mansour; Mansoor Sarfarazi; Anne H. Child; Alberto Smith; Russell Mellor; Kevin Burnand; Peter Mortimer; Steve Jeffery (Human Genetics, 2005)